1987
DOI: 10.1083/jcb.105.4.1873
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple cell adhesion receptors for collagen and fibronectin in human fibrosarcoma cells possessing unique alpha and common beta subunits.

Abstract: Abstract. Using monoclonal antibody technology and affinity chromatography we have identified four distinct classes of cell surface receptors for native collagen on a cultured human fibrosarcoma cell line, HT-1080. Two classes of monoclonal antibodies prepared against HT-1080 cells inhibited adhesion to extracellular matrix components. Class I antibodies inhibited cell adhesion to collagen, fibronectin, and iaminin. These antibodies immunoprecipitated two noncovalently linked proteins (subunits) with molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
436
2

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 687 publications
(456 citation statements)
references
References 44 publications
(62 reference statements)
18
436
2
Order By: Relevance
“…Figure 5A and B demonstrate clearly that pancreatic cancer cell adhesion and migration on type I collagen is mediated exclusively by the a 2 b 1 integrin, and that neither the a 1 , a 3 , a 5 , or a 6 integrin subunits, nor the a v b 3 or a v b 5 integrins appear to be involved in the adhesive interactions between AsPC-1, BxPC-3, CFPAC, or FG pancreatic cancer cells and type I collagen. Immunoprecipitation studies shown in Figure 4 and previous studies by us and other laboratories (Cheresh and Spiro, 1987;Wayner and Carter, 1987;Sonnenberg et al, 1988;Wayner et al, 1988Wayner et al, , 1993Grzesiak et al, 1992Grzesiak et al, , 2005aFabbri et al, 1996) demonstrate that the monoclonal antibodies used for the type I collagen inhibition studies are functional.…”
Section: Type I Collagen Promotes Maximal Haptokinetic Cell Migrationsupporting
confidence: 58%
See 1 more Smart Citation
“…Figure 5A and B demonstrate clearly that pancreatic cancer cell adhesion and migration on type I collagen is mediated exclusively by the a 2 b 1 integrin, and that neither the a 1 , a 3 , a 5 , or a 6 integrin subunits, nor the a v b 3 or a v b 5 integrins appear to be involved in the adhesive interactions between AsPC-1, BxPC-3, CFPAC, or FG pancreatic cancer cells and type I collagen. Immunoprecipitation studies shown in Figure 4 and previous studies by us and other laboratories (Cheresh and Spiro, 1987;Wayner and Carter, 1987;Sonnenberg et al, 1988;Wayner et al, 1988Wayner et al, , 1993Grzesiak et al, 1992Grzesiak et al, , 2005aFabbri et al, 1996) demonstrate that the monoclonal antibodies used for the type I collagen inhibition studies are functional.…”
Section: Type I Collagen Promotes Maximal Haptokinetic Cell Migrationsupporting
confidence: 58%
“…The function-blocking monoclonal antibodies directed against particular integrin subunits and integrins used in these studies have been described (Cheresh and Spiro, 1987;Wayner and Carter, 1987;Sonnenberg et al, 1988;Wayner et al, 1988Wayner et al, , 1993Fabbri et al, 1996), and include FB12 (a 1 ), P1E6 (a 2 ), P1B5 (a 3 ), P1D6 (a 5 ), GoH3 (a 6 ), P5D2 (b 1 ), LM609 (a v b 3 ), P1F6 (a v b 5 ), and ASC-3 (b 4 ) (Chemicon International, Temecula, CA, USA). For immunoprecipitation (IP) experiments, we used the monoclonal antibodies described above along with rabbit polyclonal antisera against the a 5 integrin subunit, which has also been described previously (Ruoslahti and Pierschbacher, 1987).…”
Section: Antibodiesmentioning
confidence: 99%
“…No increases in surface expression of the collagen-binding heparan sulfate proteoglycan, CD44/ECMR-111, were detected by immunoprecipitation or immunofluorescence ( Figure 3D and data not shown) (Wayner and Carter, 1987). Finally, because FA-K562 adhesion to FN is trypsin insensitive and RGD inhibitable, syndecan is unlikely to be the receptor mediating FA-K562 adhesion to FN (Saunders and Bernfield, 1988).…”
Section: Selection Of Fa-k562mentioning
confidence: 97%
“…Additional FN-specific sequences or conformation were also required, as FA-K562 did not adhere to plastic coated with thrombin; GRGDS peptide; or the RGD-containing proteins laminin, collagen, or fibrinogen (Figure 1 F and data not shown). Although transforming growth factor-beta (TGF-beta) has been detected in some FN preparations (Fava and McClure, 1987) and could be responsible for morphologic changes, no bioactive TGF-beta was found in the FN preparation used in this study (personal communication, Dr. A. Purchio (Wayner and Carter, 1987;Wayner et al, 1989). Cells with similar phenotypes and FNR expression levels have been independently generated three times.…”
Section: Selection Of Fa-k562mentioning
confidence: 99%
See 1 more Smart Citation